2009
DOI: 10.1016/j.vaccine.2008.09.092
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence that commercial influenza vaccines are not similar in their ability to activate human T cell responses

Abstract: We evaluated three commercial trivalent inactivated vaccines (TIVs) from the 2007-2008 season in terms of their ability to elicit in vitro T cell responses. T cell-mediated immunity may offer a more cross-reactive vaccine approach for the prevention of pandemic or epidemic influenza. Human cytotoxic T cell lines demonstrated differences in matrix protein 1 and nucleocapsid protein recognition of autologous target cells. Peripheral blood mononuclear cells stimulated with each of the TIVs showed statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…The ability of commercially available influenza vaccines to induce human T-cell responses may vary depending on the internal protein contents of vaccines from different manufacturers (12). Here we showed that TIV (GlaxoSmithKline) induced HLA-A2/M1 58-66 -tetramer ϩ CD8 ϩ T cells in 20% of HLA-2-positive individuals, as this vaccine contains a relatively high level of M protein (11).…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 79%
“…The ability of commercially available influenza vaccines to induce human T-cell responses may vary depending on the internal protein contents of vaccines from different manufacturers (12). Here we showed that TIV (GlaxoSmithKline) induced HLA-A2/M1 58-66 -tetramer ϩ CD8 ϩ T cells in 20% of HLA-2-positive individuals, as this vaccine contains a relatively high level of M protein (11).…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 79%
“…The somewhat greater antibody responses to ADV might not translate into greater protection as subunit vaccines potentially induce lesser cellular immune responses. 41 Neutralizing antibody assays would ideally have been performed with all 3 viruses and might have shed light on the elevated baseline B titers. Finally, we recognize that the seroprotection threshold (HAI titers ≥ 40) conventionally used to evaluate responses may not accurately predict protection in elderly adults, with greater antibody titers and cellular immune responses being required for protection.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, other studies have shown that TLR7 is important for the induction of a protective memory response against influenza whole inactivated vaccine (18,34,35), while split vaccines lacking intact RNAs are defective in inducing a protective antibody response (34). In addition, Co and colleagues showed that a seasonal split vaccine activated human T cells more efficiently than a subunit vaccine, which contains only the highly purified surface antigens HA and neuraminidase (NA) (11). In a separate study, Kasturi and colleagues showed that purified HA alone did not elicit virusneutralizing antibody titers, whereas the addition of a TLR7 ligand to HA increased antibody production in mice (30).…”
Section: Fig 3 Tlr7mentioning
confidence: 94%